Fungal Species and Mycotoxins Associated with Maize Ear Rots Collected from the Eastern Cape in South Africa - Jenna-Lee Price; Cobus Meyer Visagie; Hannalien Meyer; Neriman Yilmaz (Toxins, 2024)
Maize production in South Africa is concentrated in its central provinces. The Eastern Cape contributes less than 1% of total production, but is steadily increasing its production and has been identified as a priority region for future growth. In this study, we surveyed ear rots at maize farms in the Eastern Cape, and mycotoxins were determined to be present in collected samples. Fungal isolations were made from mouldy ears and species identified using morphology and DNA sequences. Cladosporium, Diplodia, Fusarium and Gibberella ear rots were observed during field work, and of these, we collected 78 samples and isolated 83 fungal strains. Fusarium was identified from Fusarium ear rot (FER) and Gibberella ear rot (GER) and Stenocarpella from Diplodia ear rot (DER) samples, respectively. Using LC-MS/MS multi-mycotoxin analysis, it was revealed that 83% of the collected samples contained mycotoxins, and 17% contained no mycotoxins. Fifty percent of samples contained multiple mycotoxins (deoxynivalenol, 15-acetyl-deoxynivalenol, diplodiatoxin and zearalenone) and 33% contained a single mycotoxin. Fusarium verticillioides was not isolated and fumonisins not detected during this survey. This study revealed that ear rots in the Eastern Cape are caused by a wide range of species that may produce various mycotoxins.